2015
DOI: 10.1186/s13075-015-0863-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abatacept on the immunogenicity of 23-valent pneumococcal polysaccharide vaccination (PPSV23) in rheumatoid arthritis patients

Abstract: IntroductionPatients with rheumatoid arthritis (RA) treated with abatacept (ABT) are at increased risk for vaccine-preventable infections. The aim of the present study is to evaluate the humoral response to 23-valent pneumococcal polysaccharide (PPSV23) vaccination in RA patients receiving ABT.MethodsThe immunogenicity study was nested within a randomized, double-blind placebo-controlled study, designed to evaluate the efficacy of the PPSV23. PPSV23 was given to 111 RA patients, who were classified into three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 30 publications
(35 reference statements)
4
33
0
2
Order By: Relevance
“…Combination of abatacept and a conventional DMARD significantly reduced the response towards the 2009 influenza vaccine [101]. Similar data have been proposed for vaccination against pneumococcus pneumoniae [102,103].…”
Section: Abataceptsupporting
confidence: 65%
“…Combination of abatacept and a conventional DMARD significantly reduced the response towards the 2009 influenza vaccine [101]. Similar data have been proposed for vaccination against pneumococcus pneumoniae [102,103].…”
Section: Abataceptsupporting
confidence: 65%
“…There were limited data to perform meta-analysis on TOC exposure on vaccine responses compared to healthy controls, although review of the literature suggests there no significant effect on PPV or influenza vaccine immunogenicity, [18,24]. Comparatively, ABA has been reported to impair the responses to pH1N1 and PPV23 response, [16,23]. To our knowledge, there has been 1 previous meta-analysis assessing the influence of antirheumatic drug therapies on influenza and pneumococcal vaccine responses, [42].…”
Section: Discussionmentioning
confidence: 99%
“…The data on ABA exposure and humoral vaccine response are conflicting. Migita et al, [23] found significantly decreased Ab response rates for 6B and combined 6B/23F SR rates in ABA exposed patients compared to MTX and RA control groups. In contrast, Alten et al , [17] described preserved SP response to PPV23 vaccination with 55.4% of ABA exposed patients achieving adequate SP response to PPV23 vaccination.…”
Section: Aba and Pneumococcal Vaccine Responsementioning
confidence: 95%
“…Given the high risk of infection in patients receiving biologic therapy, the 2015 ACR and APLAR guidelines recommended assessment of vaccination history and completion of outstanding vaccination when possible, before initiating bDMARDs. Several RCTs studied the safety and efficacy of pneumococcus, influenza, and HBV vaccination in patients receiving biologic therapy [133][134][135][136][137][138][139][140]. Biologic therapy seems to be unrelated to the side effect of the killed vaccine.…”
Section: Monitoring Strategies Before or During Use Of Bm-dards In Pamentioning
confidence: 99%